Associations of abdominal visceral and subcutaneous adipose tissue with clinical and computed tomography imaging markers of metabolic syndrome (Annals of Medical Research, 2021)
Aim: Central obesity comprises visceral (VAT) and subcutaneous (SAT) adipose tissues, which were reported to have associations with metabolic syndrome. Abdominal computed tomography (CT) scan allows evaluation of VAT, SAT, hepatosteatosis, pancreatic steatosis, and aortoiliac atherosclerosis. We aim to investigate the relationship between central obesity components (VAT, SAT) and metabolic syndrome imaging markers that are detectable on abdominal CT and the predictive power of these parameters for detecting hypertension (HT), diabetes mellitus (DM), and dyslipidemia (DL).Materials and Methods: Abdominal CT scans of 321 patients were evaluated for VAT, SAT volumes, hepatosteatosis, pancreatic steatosis, and aortoiliac atherosclerosis in this retrospective cross-sectional study. The associations of VAT, SAT, and visceral-to-subcutaneous fat (V/S) ratio with HT, DM, DL, hepatosteatosis, pancreatic steatosis, and aortoiliac atherosclerosis were investigatedby Mann-Whitney U test, Kendall's Tau-b test, and boosting linear regression analysis. Cut-off values of VAT, SAT, and V/S ratio were calculated to predict HT, DM, DL, hepatosteatosis, pancreatic steatosis, and aortoiliac atherosclerosis by receiver operating characteristic (ROC) curve analysis.Results: Increased VAT volume and V/S ratio were significantly related to HT, DM, DL, hepatosteatosis, pancreatic steatosis, and aortoiliac atherosclerosis (p
Keywords: Atherosclerosis; computed tomography; fatty liver; metabolic syndrome; subcutaneous adipose tissue; visceral adipose tissue